Deployment method of VM cluster based on graph theory for cloud resource management. Issue 5 (28th February 2017) - Xu, Bo; Peng, Zhiping; Ke, Wende; Zhong, Ming; Marcel Gates, Antonio
Abstract : Cloud computing is the next generation of computation and is regarded as the fifth utility service. A core issue of cloud computing is the deployment of virtual machine (VM). A new method had been constructed for VM cluster based on graph theory in this study. The authors first described VM cluster by energy minimisation. Then, they changed deployment of VM cluster into maximum flow minimum cut problem, added sink and source point, and found activity node. Finally, activity tail‐nodes were connected and cut formed for VM cluster. Experimental results show that the segmentation method can effectively realise the VM deployment clusters, can reduce the overall bandwidth requirements after deployment.